Proposal For A Market-Based Solution to Airport Delays - W. Tom Whalen; Dennis W. Carlton; Ken Heyer; Oliver Richard (U.S. Department of Justice, Antitrust Division, Economic Analysis Group (EAG), 2007)
With the clamor rising over airport delays and with both the Congress and the Administration considering remedies, this paper advocates the use of market mechanisms, specifically slot auctions, to promote efficient usage of airport capacity, reduce airport delays, and, more generally, promote competition.
Keywords: 330